A 5 years’ experience of a parent-baby day unit: impact on baby’s development - Moureau, Audrey; Cordemans, Louise; Gregoire, Caroline; Benoît, Pirmez; Delvenne, Veronique (Frontiers in Psychiatry, 2023)
Introduction: Psychiatric Mother-Baby Units are well established in France, United Kingdom and Australia, mostly in full-time hospitalization. Inpatient units are considered as best practice for improving outcomes for mothers and babies when the mother is experiencing severe mental illness and many studies have showed the effectiveness of care for the mother or the mother-infant relationship. Only a limited number of studies have focused on the day care setting or on the development of the baby. Our parent-baby day unit is the first day care unit in child psychiatry in Belgium. It offers specialized evaluation and therapeutic interventions focused on the baby and involves parents with mild or moderate psychiatric symptoms. The advantages of day care unit is to reduce the rupture with social and family living. Aims: The objective of this study is to evaluate the effectiveness of parent-baby day unit in prevention of babies’ developmental problems. First, we present the clinical characteristics of the population treated in the day-unit in comparison to the features presented in the literature review about mother-baby units, which usually receive full-time treatment. Then, we will identify the factors that might contribute to a positive evolution of the baby’s development. Discussion : The clinical population of the day unit is comparable to the mother-baby units in terms of psychosocial fragility but the psychopathological profile of the parents entering the day unit shows more anxiety disorder and less post-partum psychosis. The babies’ development quotient is in the average range at T1 and is maintained at T2. In the day unit, the number of symptoms as well as the relational withdrawal of the babies is reduced between T1 and T2. The quality of parent-child relationship is improved between T1 and T2. The children of the group of pejorative evolution had a lower developmental quotient at the T1 and an overrepresentation of traumatic life events. Conclusion: These results indicate that parent-baby day unit lead to positive outcomes in clinical situations with anxio-depressive parents, relational withdrawal of the babies, functional problems of the babies but not when a significant impact on the development of the baby already exists.